Der „jüdisch-christliche“ Dialog veränderte die Theologie - Fischer, Irmtraud (2016)
The volume presents a collection of papers which clearly document a theological paradigm shift during the decades after World War II. Protestant, Catholic and Jewish experts from various specialist fields of theology, such as biblical scholarship (Old Testament and New Testament), liturgics, feminist and systematic theology, as well as Jewish studies provide a diverse picture of the theological change from anti-Jewish polemics to a respectful dialogue with Judaism. Moreover, the publication offers an insight into the biographical developments of the scholars involved, and through this a piece of reflective history of theology.